Effects of gas‐phase collisions in rapid desorption of molecules from surfaces in the presence of coadsorbates - Ibrahim Ali , Noorbatcha; Lucchese, Robert R.; Zelri, Yehuda (American Institute of Physics (AIP), 1988)
The effects of gas‐phase collisions in mixtures of gases rapidly desorbed from surfaces are studied using direct Monte Carlo techniques. The results are compared with the effects observed in the desorption of pure gases under similar conditions. The translational energy distribution of the desorbed particles are found to deviate from the Boltzmann distribution and are found to be well represented by ellipsoidal Boltzmann distributions. In this respect the rapid desorption process is found to have similarities to the expansion of gases in nozzle sources. The influence of mass, internal degrees of freedom, and surface coverage of the adsorbates on the focusing, accelerating, and cooling effects due to gas‐phase collisions are analyzed. The presence of molecules with active internal degrees of freedom is found to increase the average number of collisions experienced by the rapidly desorbed molecules. However, the influence of this increased number of collisions on the focusing effects due to gas‐phase collisions is less pronounced compared to the focusing effects due to collisions between the desorbed atoms. In a gas mixture containing molecules as the minor constituents (10%) and atoms as the major constituents (90%), atoms are found to be more focused towards the surface normal than the molecules and the mean translational energies of the molecules are found to be less than those calculated in the desorption of pure molecules under similar conditions. The presence of atoms in the desorbed gas mixture is found to increase the most probable speed of the desorbing molecules and this accelerating effect increases with decrease in the mass of the coadsorbed atoms. The light atoms are found to be more efficient than heavy atoms in cooling the internal degrees of freedom.